Bromide intoxication in a 3‐year‐old Thoroughbred filly. (7th December 2021) - Sacks, M.; Byrne, D. P.; McConnell, E. J.
Summary: A 3‐year‐old Thoroughbred filly presented with a several‐month history of weight loss, polydipsia and polyuria, intermittent diarrhoea and behavioural changes and intermittently uncoordinated gait. Neurological examination revealed hyperexcitability, bilaterally reduced pupillary light reflexes and quadrilateral ataxia with proprioceptive deficits more obvious in the forelimbs than in the hindlimbs. A multifocal neurological lesion was suspected. The laboratory finding of a persistent hyperchloraemia and an apparent negative anion gap prompted measurement of serum bromide concentration and subsequently confirmed bromide intoxication. Further questioning of the trainer revealed that the filly had been administered oral potassium bromide for behavioural modification over several months. Clinical signs of bromide intoxication resolved within 20 days following the last bromide administration, without specific medical intervention. This case report describes the risk of inadvertent bromide overdosing in horses and highlights the need for control of bromide use in the equine industry.